Sludge reduction in an activated sludge wastewater treatment process - Seretlo, Manana Alinah (Vaal University of Technology, 2022)
Sludge process reduction activated sludge (SPRAS) is usually the preferred treatment method at wastewater treatment plants (WWTPs) and for waste activated sludge (WAS), with the advantage of effective sludge reduction. However, the recalcitrant compounds such as pollutants and solids present in the wastewaters are removed by SPRAS process and enhanced sludge reduction with no increment of chemicals, thus yielding the required quality of effluent for reuse. The sludge treatment techniques such as thickening, dewatering, digestion, and final disposal are complex and costly. The cost of dealing with WAS accounts for 30-50% of wastewater treatment total costs (WWTPs). The technology has been successfully implemented in China, with outstanding results. Four SPRAS plants in China, each with a capacity of 20 000 m3/day, have successfully treated municipal sewage to a reusable quality with no zero-sludge production. The cost of wastewater treatment has significantly decreased due to the implemented technology. Moreover, South Africa has harmonized with the SPRAS technology; three SPRAS package pilot plants have been installed. The plants are located in Eastern Cape towns of Cradock and Kirkwood and Free State's Glen Agricultural College. Comparing the activated sludge process, which is commonly used in South Africa for treating municipal sewage, the SPRAS units have demonstrated more remarkable performance. Therefore, the study aims to evaluate the performance of the SPRAS technology, which is installed at Glen Agricultural College in Free State province, South Africa. The installation aims to ensure that the SPRAS system operation is sufficient to produce consistently high-quality treated water for reuse and near-zero sludge discharge and reduce operating costs. SPRAS technology installed at Glen Agricultural College in Free State province, South Africa, produces the sludge yield of the SPRAS plant of 0.026 kg TSS/kg COD which was much lower than the sludge yield of a conventional activated sludge process of 1.2 kg TSS/kg COD. Therefore, the SPRAS plant can achieve > 95% sludge reduction with ultra-Violet (UV) disinfection of the treated wastewater reduced the E. coli concentration to < 10 counts/100 mL which suggest that the treated wastewater can be safely reused in agriculture without adverse infections. The power consumption of SPRAS plant is 1.2 kWh/m3, which is comparable to that of MBR. However, MBR incurs additional cost of sludge handling while SPRAS achieves zero sludge discharge.
M. Tech. (Department of Chemical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Sludge process reduction activated sludge (SPRAS); Wastewater treatment plants (WWTP); Waste activated sludge (WAS); Pollutants; Sludge reduction; SPRAS technology; SPRAS package pilot plants; Municipal wastewater treatment; Sludge disposal; Mechanical treatment; Chemical treatment; Dissertations, Academic -- South Africa.; Sewage sludge -- South Africa.; Sewage -- Purification.; Sewage sludge -- Technological innovations.; Water-supply engineering -- Technological innovations.; Sewage disposal --Technological innovations.